Box and block test, hand grip strength and nine‐hole peg test: correlations between three upper limb objective measures in multiple sclerosis. (1st August 2020) - Solaro, C.; Di Giovanni, R.; Grange, E.; Mueller, M.; Messmer Uccelli, M.; Bertoni, R.; Brichetto, G.; Tacchino, A.; Patti, F.; Pappalardo, A.; Prosperini, L.; Castelli, L.; et al.
Abstract : Background and purpose: Limited data are available in the literature for upper limb impairment in multiple sclerosis (MS). This study aimed to report the distribution of values of hand grip strength (HGS), of the box and block test (BBT) and of the nine‐hole peg test (9HPT) correlated with demographic and clinical data in subjects with MS. Methods: This study involved five Italian neurological centres. The inclusion criteria were age ≥ 18, MS diagnosis, stable disease phase, right‐hand dominance. All subjects underwent HGS, BBT and 9‐HPT evaluation. Results: In all, 202 subjects with MS were enrolled: 137 females; mean age 48.4 years; mean Expanded Disability Status Scale (EDSS) 4.17; mean disease duration 14.12 years; disease course 129 relapsing–remitting, 21 primary progressive and 52 secondary progressive MS subjects; mean right HGS 25.3 kg, left 23.2 kg; mean right BBT 45.7 blocks, left 44.9 blocks; mean right 9‐HPT 30.7 s, left 33.4 s. All results were statistically significantly different compared to healthy controls. HGS, BBT and 9‐HPT were associated with age, EDSS and disease duration, whilst disease course correlated with BBT and 9‐HPT. The BBT and 9‐HPT scores significantly differed according to level of disability (EDSS ≤3.0, 3.5–5.5, ≥6.0). Conclusion: Hand grip strength and BBT value distribution in a large MS population is reported. Correlations between HGS, BBT and 9‐HPT were generally low.